Immigration Detention Supervision Urgency - Cinde Salsabiil; Dwi Nuryani; Happy Herlambang (Journal of Law and Border Protection, 2019)
World War II was a war between the Allied Powers and the Axis Powers, both of which had extraordinary military power. Seeing the post-World War II conditions, many people lost their homes and families so that in order to realize human rights, the international community agreed to form the United Nations (UN) or the United Nations (UN) with the aim of strengthening international cooperation and preventing conflicts. upcoming conflict. In terms of protecting refugee rights, the United Nations established the legal basis for the Geneva Convention 1951 which is a guideline for the international community in providing protection for refugees. Australia was one of the countries that took part in ratifying the Geneva convention of 1951, while Indonesia was not one of the countries that ratified the convention. However, due to the geographic location of Indonesia as opposed to Australia, Indonesia has had the impact, namely the number of asylum seekers waiting for their refugee status and some of them are not clear because they are not included in the category of refugees by UNHCR. So that the author will explain how important the supervision of refugees in Indonesia is by the Immigration Detention Center or often referred to as Rudenim. In the Duties and Functions of Rudenim there is already a supervisory function but the subject of such supervision is detainees, while in Presidential Regulation No. 125 of 2016 concerning the Handling of Refugees from Abroad, Rudenim has the duty to supervise refugees in Indonesia, so that there are discrepancies between the regulations of the Rudenim Administration and the legal basis governing the handling of these refugees.